The Application of Concept Restoration of Justice in the Perspective of Local Wisdom in the Samin Tribe - Sutiono; Anshori; Shofiyul Umam; Jibril (Inovasi Pratama Internasional. Ltd, 2023)
This research examines the application of the concept of restoration of justice in the perspective of local wisdom in the Samin tribe. Restorative Justice is basically a method in handling cases to uphold the values ​​of justice in a legal event by carrying out legal remedies. In maintaining justice, other community groups, especially the Samin people, also have their own perspective. The Samin tribe has the wisdom to behave well to maintain social order in the life of its people. independent in dealing with the process of life. The writing method used is the Juridical Empirical writing method. The formulation of the problem in this study is: How is the concept of restorative justice used by law enforcement in Indonesia. Is restorative justice also a local wisdom practice in the Samin community. Then the restoration of justice in its application has been carried out by law enforcers, especially in mild cases, then basically the Samin people with their local wisdom are very relevant to the concept of restoration of justice.